Nickel-catalyzed regio- and enantio-selective Markovnikov hydromonofluoroalkylation of 1, 3-dienes. Issue 42 (19th October 2022) - Liao, Ling; Zhang, Ying; Wu, Zhong-Wei; Ye, Zhong-Tian; Zhang, Xue-Xin; Chen, Guangying; Yu, Jin-Sheng
Abstract : We report a highly enantio- and regio-selective Markovnikov hydromonofluoro(methyl)alkylation of 1, 3-dienes using chiral Ni catalysis, allowing access to chiral allylic compounds bearing a CH2 F, CD2 F or monofluoroalkyl group at the stereocenter. Abstract : A highly enantio- and regio-selective Markovnikov hydromonofluoro(methyl)alkylation of 1, 3-dienes was developed using redox-neutral nickel catalysis. It provided a facile strategy to construct diverse monofluoromethyl- or monofluoroalkyl-containing chiral allylic molecules. Notably, this represents the first catalytic asymmetric Markovnikov hydrofluoroalkylation of olefins. The practicability of this methodology is further highlighted by its broad substrate scope, mild base-free conditions, excellent enantio- and regio-selectivity, and diversified product elaborations to access useful fluorinated building blocks.